DAPATKAH KITA MEMPREDIKSI PERUBAHAN HARGA SAHAM? - Edi Pranyoto (Jurnal Bisnis Darmajaya, 2016)
The purpose of this paper is to study the behavior of stock prices at LQ45 based on the behavior of stock prices at LQ45 itself in the period 2013 until 2015. The sample in this study is a company incorporated at LQ 45 index from 2013 until 2015. The basic model of the data used is time series data. Time series data often indicates conditions are not stationary at the current level, but often shows a stationary through diferensi process. Then, the data will be analyzed using Model Autoregressive Integrated Moving Average (ARIMA / Box-Jenkins). Based on the test results showed that the stock price data at LQ45 in a random and white noise, so there is no dependence on the company's stock price changes at LQ 45 index.Key words : Efficient Market, Random Walk, White Noise